PENGARUH RETURN ON ASSET DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PT ANEKA TAMBANG Tbk (ANTAM) PERIODE 2013 – 2023 - Dara Lisnawati; Eni Puji Astuti (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effect of Return On Asset (ROA) and Current Ratio (CR) on Share Price at PT Aneka Tambang Tbk (ANTAM) for the period 2013-2023. The research method used is quantitative with data analysis techniques including descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS software assistance. The data used is secondary data in the form of annual financial reports of PT Aneka Tambang Tbk from 2013 to 2023 obtained from the company's official website and other reliable sources. The sample of this study is all financial statements of PT Aneka Tambang Tbk during that period. The results showed that partially, Return On Assets (ROA) has a positive and significant effect on stock prices, with a t_hitung value (3.078) > t_table (2.306) and a significance value of 0.015 <0.05, which means that Return On Assets has a partial effect on Stock Price.... On the other hand, Current Ratio (CR) has no effect on stock prices with a t_hitung value (-0.474) < t_table (2.306) and a significance value of 0.648 > 0.05, it can be concluded that CR is rejected, which means that Current Ratio has no partial effect on Stock Price. Simultaneously, return on assets (ROA) and Current ratio (CR) have a significant effect on stock prices, as evidenced by the value of Fcount (5.124) > Ftable (4.459) and the significance value (0.037) <0.05.